Interest Rate Spreads in the Eastern Caribbean - Randall, Ruby (IMF Working Papers; Working Paper, 1998)
This paper examines interest rate spreads in the Eastern Caribbean and seeks to explain why they are persistently high by comparison with other low-inflation countries. The paper concludes that operating costs appear to be a key determinant of observed interest rate spreads, giving rise to the policy recommendation that efforts to expand the market size of efficient banks might help pave the way for greater efficiency.